Diagnosing Mild Forms of Anorectal Malformation With Anorectal Manometry: A Prospective Study. (23rd March 2023) - den Hollander, Venla E.C.; Gerritsen, Steffie; van Dijk, Tonnis H.; Trzpis, Monika; Broens, Paul M.A.
Abstract : INTRODUCTION: Rectoperineal congenital anorectal malformations (CARMs) are diagnosed by examining the perineum, combined with electric stimulation (ES) of the anal sphincter performed under anesthesia. This procedure may be troublesome because it is based on the observed contractibility of the sphincter. We aimed to add 3-dimensional high-resolution anorectal manometry (3D-HRAM) to the procedure and to assess its value for diagnosing rectoperineal forms of CARM. METHODS: We prospectively included 66 patients younger than 24 months who presented with constipation and were suspected of CARM, idiopathic constipation, or Hirschsprung disease. The patients were assessed between 2015 and 2021 at University Medical Center Groningen, the Netherlands. All patients underwent 3D-HRAM, followed by the standard diagnostic procedure for either CARM or Hirschsprung disease. RESULTS: Of the 51 patients who underwent both 3D-HRAM and ES, we observed that patients with rectoperineal CARM revealed a pressure gap along the anterior part of the anal sphincter. Based on this observation, we diagnosed 35 patients with CARM. Subsequently, all 35 diagnoses were confirmed with ES. Sixteen patients were diagnosed as not having CARM, 100% of whom were in agreement with the gold standard—ES. Both the specificity and sensitivity of 3D-HRAM for diagnosing rectoperineal CARM were 100%. DISCUSSION: We consider 3D-HRAM a reliable tool for diagnosing and excluding rectoperineal CARM. Using this method in patients suspected of CARM might keep infants from undergoing unnecessary interventions requiring anesthetics, such as ES. By providing objective insight into the functional capabilities of the anal sphincter, anorectal manometry adds to the diagnosis.